Real-Time Reconstruction of the Complex Field of Phase Objects Based on Off-Axis Interferometry - Li, Xiang; Qin, Guanyuan; Yu, Wenhui; Li, Huixian; Hu, Rui; Qu, Junle; Liu, Liwei (Frontiers in Physics, 2022)
Quantitative phase imaging (QPI) can acquire dynamic data from living cells without the need for physical contact. We presented a real-time and stable dynamic imaging system for recording complex fields of transparent samples by using Fourier transform based on off-axis interferometry. The temporal and spatial phase sensitivity of the system was evaluated. Benefit from the ability to record the dynamic phase and phase profile of a specimen, a standard sample (polystyrene microspheres) is investigated to demonstrate the efficiency of this imaging system and we have observed the variation of erythrocyte membrane during Red Blood Cells (RBCs) spontaneous hemolysis with different mediums. Experimental results indicate that the phase of non-anticoagulant RBC changed apparently than anticoagulant RBC and the system could be applied to real-time noninvasive and label-free identification of living cells.